2022
DOI: 10.1093/jac/dkac242
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-concept, rapid, instrument-free molecular detection of Neisseria gonorrhoeae and ciprofloxacin susceptibility

Abstract: Objectives To develop instrument-free point-of-care methods using recombinase polymerase amplification (RPA) technology coupled with a simple lateral flow detection system to detect Neisseria gonorrhoeae and susceptibility to ciprofloxacin. Methods For identification of gonococcal infection, an RPA-based method was developed targeting the gonococcal porA pseudogene (NG-porA-RPA). For ciprofloxacin susceptibility, predictive W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[86][87][88][89][90][91][92] Ayfan et al reported the rapid and compact molecular detection assay of Neisseria gonorrhoeae and ciprofloxacin susceptibility cases by combining an RPA assay with LFA-mediated detection. 93 Abdou Mohamed et al were among the early researchers 94 to develop a multiplex nucleic acid enzyme-gold nanoparticle-based diagnostic platform for identifying the target pathogens alongside the respective antibiotic resistant genes within a span of 2 hours. Their test deployed an enzyme comprising two nucleic acid strands instead of amino acids, having the capability of selective DNA cleaving.…”
Section: Some Isothermal Naats Introduced For Infectious Disease Diag...mentioning
confidence: 99%
“…[86][87][88][89][90][91][92] Ayfan et al reported the rapid and compact molecular detection assay of Neisseria gonorrhoeae and ciprofloxacin susceptibility cases by combining an RPA assay with LFA-mediated detection. 93 Abdou Mohamed et al were among the early researchers 94 to develop a multiplex nucleic acid enzyme-gold nanoparticle-based diagnostic platform for identifying the target pathogens alongside the respective antibiotic resistant genes within a span of 2 hours. Their test deployed an enzyme comprising two nucleic acid strands instead of amino acids, having the capability of selective DNA cleaving.…”
Section: Some Isothermal Naats Introduced For Infectious Disease Diag...mentioning
confidence: 99%